Evaluation of Fire Mitigation and Fire Protection in a Cooking Oil Processing Company - Dita Rahmawati (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: A fire ever took place in the early 2019 in one of the cooking oil processing companies in Sidoarjo. This is because the company had a storage warehouse of cartons, jerry cans, and plastic packaging,categorized into flammable materials. The flame was suspected from rags that were exposed to spills of cooking oil, oxygen, and heat from direct sunlight and cigarette butts. The research objectives of this study are to study the implementation of fire mitigation unit and also active and passive fire protection facilities in one of the cooking oil processing companies in Sidoarjo. Methods: The study was observational with a cross sectional design and was analyzed descriptively. It evaluated the suitability of the observational data with the Minister of Manpower Decree Number 186 Year 1999, Minister of Public Work Regulation Number 26 Year 2008, and Minister of Manpower and Transmigration Regulation Number 4 Year 1980. The variables consisted of 1 fire mitigation unit, 1 waterway, 34 fire extinguishers, 7 emergency exits, 41 evacuation routes, and 2 assembly points. Data were collected through the observation and document study. Then, the data were presented in a narrative form. Results: 79.2% of fire mitigation units, 77.6% of active fire protection facilities, and 57.1% of passive fire protection facilities in one of the cooking oil processing companies in Sidoarjo are appropriate with the applicable regulations. Conclusion: The fulfillment level of fire mitigation units and active fire protection facilities are high, while the fulfillment level of passive fire protection facilities are moderate.Keywords: active and passive fire protection, evaluation, fire mitigation